Review grain yield and nitrogen use efficiency in rice production regions in China - Sheng-guo CHE; Bing-qiang ZHAO; Yan-ting LI; Liang YUAN; Wei LI; Zhi-an LIN; Shu-wen HU; Bing SHEN (Journal of Integrative Agriculture)
As one of the staple food crops, rice (Oryza sativa L.) is widely cultivated across China, which plays a critical role in guaranteeing national food security. Most previous studies on grain yield or/and nitrogen use efficiency (NUE) of rice in China often involved site-specific field experiments, or small regions with insufficient data, which limited the representation for the current rice production regions. In this study, a database covering a wide range of climate conditions, soil types and field managements across China, was developed to estimate rice grain yield and NUE in various rice production regions in China and to evaluate the relationships between N rates and grain yield, NUE. According to the database for rice, the values of grain yield, plant N accumulation, N harvest index (HIN), indigenous N supply (INS), internal N efficiency (IEN), reciprocal internal N efficiency (RIEN), agronomic N use efficiency (AEN), partial N factor productivity (PEPN), physiological N efficiency (PEN), and recover efficiency of applied N (REN) averaged 7.69 t ha−1, 152 kg ha−1, 0.64 kg kg−1, 94.1 kg kg−1, 53.9 kg kg−1, 1.98 kg kg−1, 12.6 kg kg−1, 48.6 kg kg−1, 33.8 kg kg−1, and 39.3%, respectively. However, the corresponding values all varied tremendously with large variation. Rice planting regions and N rates had significant influence on grain yield, N uptake and NUE values. Considering all observations, N rates of 200 to 250 kg ha−1 commonly achieved higher rice grain yield compared to less than 200 kg N ha−1 and more than 250 kg N ha−1 at most rice planting regions. At N rates of 200 to 250 kg ha−1, significant positive linear relationships were observed between rice grain yield and AEN, PEN, REN, IEN, and PFPN, and 46.49, 24.64, 7.94, 17.84, and 88.24% of the variation in AEN, PEN, REN, IEN, and PFPN could be explained by grain yield, respectively. In conclusion, in a reasonable range of N application, an increase in grain yield can be achieved accompanying by an acceptable NUE.